A Distributed Resource-Management Approach in MANETs - B., Pahlevanzadeh; T.C., Wan; R., Budiato; M. Kadhum, Mohammed; S.A., Hosseini Seno (2008)
Mobile ad hoc network (MANET) is an infrastructure less network, in where all mobile nodes are free for any movement to any side.